COURT INTERPRETING AT DENPASAR COURT - Puspani, Ida Ayu Made; Sutjiati Beratha, Ni Luh; Putra Yadnya, Ida Bagus; Pastika, I Wayan (e-Journal of Linguistics; Vol. 5. Januari 2011 No. 2)
This is a research on interpreting (oral translation) on a criminal case ofdrug user in the court proceedings at Denpasar Court. The study of theinterpreting is concerned with two-ways rendition from Indonesian into Englishand vice-versa. The study is related to: (1) the description of modes of interpretingapplied by the interpreter, (2) the application of translation strategies: shift,addition and deletion of information, (3) factors that underlie the application ofthe strategies, and (4) the impact of the application of those strategies towards thequality of the interpreting.The methodology applied in this study is qualitative based on eclectictheories (translation, syntax, semantics and pragmatics). The utilization of thetheories is in accordance with the type of the data analyzed in regard to thetranslation phenomena as an applied study and its complexity.The interpreting at court applied the consecutive and simultaneous modes.The strategy of shift was applied when there were differences in structure betweenthe source and the target languages. Addition of information was used when theinterpreter emphasized the message of the source language in the target language.The deletion of information applied if the context in the target language has beencovered, and it was not necessary for the interpreter to interpret the same thingbecause the message of the source language was pragmatically implied in thetarget language.The factors which underlie the application of the interpreting strategies incourt interpreting were communication factor and the differences in the languagesystems between the source and the target languages. The impact of the use of thestrategies towards the quality of the interpreting happened when the interpretationof the source language message into the message of the target language and themessage in the source language was not completely render into the targetlanguage.The novelties of the research are: (1) relevance theory and its four maximsof communication can be applied to analyse equivalence of meaning of SLmessage rendered into the TL message Sperber and Wilson (1995), (2) theapplication of consecutive mode of interpreting can render more accuraterendition compared to the simultaneous mode, (3) the interpreter applied the strategies of shift, addition and deletion of information in the process ofinterpreting in court proceedings, and (4) some mistakes were found in theinterpretation of Indonesian legal terms into English such as: KUHAP (was nottranslated), BAP (was translated into brief), sita (was translated into seize), andayat (was not translated). The translation of those terms should be: IndonesianCriminal Code, the minutes of investigation, confiscate, and paragraph.
Keywords: interpreting, consecutive, simultaneous, and strategy